Disposable sensors for environmental monitoring of lead, cadmium and mercury - Duarte, Kátia
Miniaturization is an increasing trend in the field of analytical chemistry as a response to the need to develop new analytical techniques for food, clinical, and environmental applications. There is therefore also an increasing trend towards the use of miniaturized disposable sensors, which are inexpensive and designed to be one-shot and do not require pre-treatment prior to use or cleaning between measurements. This review describes disposable sensors for detection of lead, cadmium and mercury in the environment, taking into account their analytical performance. Further, we also discuss the role of certain factors, such as the immobilization procedure and surface modification affecting the analytical characteristics of sensors. Finally, we comment on future applications and potential research interest in this field.